2019
DOI: 10.1108/ijopm-05-2017-0294
|View full text |Cite
|
Sign up to set email alerts
|

“Power to the workers”

Abstract: Purpose The purpose of this paper is to reveal how information and communication technology (ICT) can empower shop floor workers in collaborative manufacturing environments. Design/methodology/approach The authors gather data from a mobile maintenance department of a steel manufacturing company and apply the method of a scenario-based design. The authors use data from interviews, observations and company documents to create problem and activity scenarios. The authors also demonstrate the development of a wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 53 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…Digital applications have previously been found to strengthen the empowerment of the individual if the individual receives the proper information, guidance, and feedback from colleagues and supervisors (Leyer et al 2019). We contribute to this field by adding findings about the importance of well-functioning feedback-loops that also include the designers/developers.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Digital applications have previously been found to strengthen the empowerment of the individual if the individual receives the proper information, guidance, and feedback from colleagues and supervisors (Leyer et al 2019). We contribute to this field by adding findings about the importance of well-functioning feedback-loops that also include the designers/developers.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has argued that a worker-centred approach and user involvement are important principles in the processes of developing digital tools (Leyer et al 2019;Signoretti et al 2019;Vilkki 2010). However, we find that the principle of involvement referred to in the previous literature is often too general.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the moderating effect of team psychological empowerment on the relationship between abusive supervision and engagement (Kirrane, Kilroy, & O'Connor, 2019). What is very specific to knowledge workers category, the empowerment is a technical action realized via digital solutions (Schneckenberg, 2009;Leyer, Richter, & Steinhüser, 2019). Peluso, Innocenti and Pilati (2017) empirical study revealed that the work environment has a very strong motivating effect on knowledge workers as an element of total reward system.…”
Section: Workplace Empowermentmentioning
confidence: 99%